(untitled) (UNED Research Journal, 2022)
Introduction: Avian typhoid and pullorosis, diseases caused by Salmonella enterica subsp. enterica (Gallinarum serotype, Gallinarum and Pullorum biotypes), cause high mortality in poultry and generate large economic losses. Objective: To optimize molecular techniques, such as endpoint PCR and real-time PCR (qPCR), to detect avian typhoid and pullorosis. Methods: We used control bacterial strains, isolates and tissues from birds infected with Salmonella Gallinarum to standardize detection with both techniques. Results: For the endpoint PCR, we obtained 100% repeatability, specificity and sensitivity, and a Kappa value of 0.98 for reproducibility; for qPCR, 103% efficiency with a variation under 6% in repeatability and reproducibility. The detection limit for genomic DNA was 6.4 pg/μL and the limit for the number of viable cells was 3x102 CFU/mL for endpoint PCR, and 10 DNA copies per reaction for qPCR. We also confirmed the identity of S. Gallinarum, and was reduced. We reduced the detection time to about 48 hours. Conclusion: We optimized a molecular technique for rapid, reliable and sensitive detection of Salmonella Gallinarum/Pullorum, which reduces the waiting time to take action in cases of clinical suspicion and possible outbreaks.